Foot and ankle in rheumatoid arthritis - Bouysset, Maurice; Tourné, Yves.; Tillmann, Karl.; SpringerLink (Online service) (Paris : Springer Paris : Imprint: Springer, 2006)
One of the earliest signs of rheumatoid arthritis may be pain in the foot. However, this part of the body is very often neglected during clinical assessment of the illness in favour of the articulations of the upper limbs, knees and hips. Nevertheless, it appears evident that a detailed clinical examination of the forefoot, ankle and heel could be useful in order to get closer to a rheumatological diagnosis. Thanks to blood tests and conventional imaging, completed with a scanner or MRI if needed, every doctor should be in a position to detect the beginning of rheumatoid arthritis in the foot or ankle. As well as its diagnostic contribution, this book broaches the theme of the most recent medicinal treatments, that of orthoses, made-to-measure shoes (the prescription of which practitioners and the rheumatologists often hand over to the orthopaedic surgeons), and finally that of local injections. These elements constitute the main treatment of the rheumatoid foot. Taking care of the ill subject does not necessarily stop there and a surgeon may need to operate on the forefoot, which is more common, or on the mid-foot or the ankle.
Diagnosis of rheumatoid arthritis at an early stage -- The rheumatoid foot. Pathomechanics, clinical and radiological features. Therapeutic conditions -- Some reflections on pathomechanics of the rheumatoid foot and ankle -- CT and MRI in rheumatoid arthritis (midfoot, hindfoot and ankle) -- Management of the patient with rheumatoid arthritis -- Footwear for the rheumatoid foot and ankle -- Corticosteroid injections and synoviortheses of the foot and ankle in rheumatoid arthritis -- Forefoot surgery for rheumatoid arthritis -- Hindfoot surgery for rheumatoid arthritis -- Points of view about synovectomy of the ankle joint in rheumatoid arthritis -- Total ankle replacement. History, evolution of concepts, designs and surgical technique -- Some reflections about the evolution of ankle prosthesis -- Total ankle replacement in rheumatoid arthritis: treatment strategy -- Respective indications of talocrural arthrodesis and ankle prosthesis with different situations in rheumatoid arthritis -- Surgical strategy in surgery of the lower limb in rheumatoid arthritis -- Surgery of the foot and ankle in patients with rheumatoid arthritis: some reflexions.
Keywords: Orthopedics; Rheumatology; Surgical Orthopedics; Rheumatology